2022
DOI: 10.1371/journal.pone.0274466
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological profile of cervical punch biopsies and risk factors associated with high-grade cervical precancerous lesions and cancer in northwest Ethiopia

Abstract: Introduction Cervical cancer is an important public health problem in Ethiopia. However, the disease is not well characterized and studied in various parts of the country. This study was designed to describe the histopathological profile of cervical biopsies and to identify risk factors associated with high-grade cervical lesions and cancer (CIN2+C). Methods A cross-sectional study was conducted at Felege Hiwot Compressive Specialized Hospital (FHCSH) between 1 March 2019 and 30 October 2021. A structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(56 reference statements)
0
3
0
3
Order By: Relevance
“…Similarly, a study performed in India showed that cervical intraepithelial neoplasia (CIN) 1 was diagnosed in 36.1% of patients, followed by CIN 2 (33.3%) and CIN 3 (30.6%) [ 20 ]. Likewise, a study done in northwestern Ethiopia on 335 cases, showed that cervical intraepithelial neoplasia (CIN)-1, CIN-2, and CIN-3 accounted for 40(11.9%), 12(3.6%), and 12(3.6%), respectively [ 37 ]. Our findings are consistent with this and other similar studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study performed in India showed that cervical intraepithelial neoplasia (CIN) 1 was diagnosed in 36.1% of patients, followed by CIN 2 (33.3%) and CIN 3 (30.6%) [ 20 ]. Likewise, a study done in northwestern Ethiopia on 335 cases, showed that cervical intraepithelial neoplasia (CIN)-1, CIN-2, and CIN-3 accounted for 40(11.9%), 12(3.6%), and 12(3.6%), respectively [ 37 ]. Our findings are consistent with this and other similar studies.…”
Section: Resultsmentioning
confidence: 99%
“…Частая смена половых партнеров и, как следствие, высокий риск присоединения ИППП также относятся к общеизвестным факторам риска рака и предрака шейки матки, в этих условиях ВПЧ быстрее переходит из свободной в эписомальную форму и запускает процесс трансформации клеток эпителия шейки матки. Особенно опасно длительное течение инфекционного заболевания с переходом в хроническую форму, когда пациентка не предъявляет жалоб на приеме у акушера-гинеколога, а правильный диагноз возможен только после проведения дополнительных методов исследования [21][22][23][24][25].…”
Section: Discussionunclassified
“…Самым бесспорным является факт наличия ВПЧ у пациенток с предраковыми заболеваниями шейки матки. В нашем исследовании ВПЧ встречался как в группе женщин с CIN (43,3 %), так и в группе Уральский медицинский журнал umjusmu.ru Оригинальная статья женщин со здоровой шейкой матки (16,7 %), поэтому поиск данных о причине развития CIN в условиях наличия ВПЧ у одних женщин и отсутствия заболевания в этих же условиях у других женщин продолжается; пока многие исследователи связывают риск формирования инвазии с дефектом местного иммунитета [21][22][23][24][25].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As the primary symptoms of CESC are often undetectable, the disease progression may continue for 10 years. A neglect of routine physical examinations can lead to late diagnosis, thus missing the optimal period for treatment [ 17 , 18 ]. Consequently, the accuracy of the initial diagnosis is of major importance.…”
Section: Discussionmentioning
confidence: 99%